An index of authors’ popularity for Internet encyclopedia - Lande, Dmitry; Andrushchenko, Valentyna; Balagura, Iryna (National Technical University «KhPI», 2017)
The new index of the author‘s popularity estimation is represented in the paper. The index is calculated on the basis of Wikipedia encyclopedia analysis (Wiki-Index–WI). Unlike the conventional existed citation indices, the suggested mark allows to evaluate not only the popularity of the author, as it can be done by means of calculating the general citation number or by the Hirsch index, which is often used to measure the author‘s research rate. The index gives an opportunity to estimate the author‘s popularity, his/her influence within the sought-after area ―knowledge area‖ in the Internet – in the Wikipedia. There are proposed algorithms and the technique of the Wiki-Index calculation through the network encyclopedia sounding, the exemplified calculations of the index for the prominent researchers, and also the methods of the information networks formation – models of the subject domains by the automatic monitoring and networks information reference resources analysis.
Keywords: Wikipedia; Author‘s popularity estimation; Wiki- Index; Information networks; Subject domains